A systematic literature review to explore traceability and lifecycle relationship. Issue 15 (2nd August 2020) - Corallo, Angelo; Latino, Maria Elena; Menegoli, Marta; Pontrandolfo, Pierpaolo
Abstract : Traceability is the ability to follow a product along its lifecycle. It ensures product safety and quality along the supply chain, managing information generated by several players. Even though regulations establish the information that has to be traced, each player generates much more product (and process) information, which could be used to add value to products, with respect to, not only traceability, but also the lifecycle approach. However, the concepts do not appear to be immediately related in scientific panorama. This paper aims to explore the relationship between traceability and lifecycle through a systematic literature review. Six industries (Software, Manufacturing, Automotive, Automation, Aircraft, and Aerospace) and seven subject areas (Software engineering; System engineering; Industry 4.0; New product development; Process management; Data Management; and Environmental sustainability) were identified through bibliometric analysis. To better explore this relationship in the context of the food industry, a content analysis on lead papers' sample was performed to identify traceability and lifecycle definitions, methodologies and technologies and their relation. The results of the work, synthetised in a proposed research map, will be of interest to those who are approaching the subject for the first time, and for companies involved in product lifecycle management and food traceability.